An ion-implanted InP receiver for polarization resolved terahertz spectroscopy. - Castro-Camus, E; Lloyd-Hughes, J; Fu, L; Tan, H; Jagadish, C; Johnston, M (Optical Society of American (OSA), 2007)
We report on the construction, optical alignment and performance of a receiver which is capable of recording the full polarization state of coherent terahertz radiation. The photoconductive detector was fabricated on InP which had been implanted with Fe(+) ions. The device operated successfully when it was gated with near infrared femtosecond pulses from either a Ti:sapphire laser oscillator or a 1 kHz regenerative laser amplifier. When illuminated with terahertz radiation from a typical photoconductive source, the optimized device had a signal to noise figure of 100:1 with a usable spectral bandwidth of up to 4 THz. The device was shown to be very sensitive to terahertz polarization, being able to resolve changes in polarization of 0.34 degrees. Additionally, we have demonstrated the usefulness of this device for (i) polarization sensitive terahertz spectroscopy, by measuring the birefringence of quartz and (ii) terahertz emission experiments, by measuring the polarization dependence of radiation generated by optical rectification in (110)-ZnTe.